Expertise, Vagueness and Maxims of Experience in Tax Avoidance Cases - Osorio Morales, Hugo (2024)
The main objective of this research is to analyze vagueness as an evidentiary problem in tax avoidance cases, evaluating its impact on the ability of the adjudicating body to determine whether the specific facts of a case can be classified as tax avoidance. The work also aims to explain that the expertise of tax law applicators is relevant, both to identify and resolve problems of vagueness and to make and evaluate maxims of experience in establishing the facts in this type of cases. To this effect, in the first section, an attempt is made to delimit the concept of “tax avoidance” and a definition of tax avoidance consistent with the dominant linguistic uses in current Spanish and Chilean dogmatics. The second section analyzes the role of vagueness, frequently used in the application of general anti-avoidance rules, to combat tax avoidance. It is concluded that it is a kind of vagueness called “extravagant”, used intentionally by the legislator to try to regulate the innumerable forms in which the avoidance phenomenon can be manifested. The third section studies the importance of expertise and the maxims of experience to distinguish an elusive case from a non-elusive case.